![image](https://tex.z-dn.net/?f=x%5E8+%5Cgeq+0%0A%5C%5C%5C+x%5E4+%5Cgeq+0%0A%5C%5C%5C%0Ax%5E8%2Bx%5E4%2B10%3E0)
0" alt="x^8 \geq 0
\\\ x^4 \geq 0
\\\
x^8+x^4+10>0" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+%5Cfrac%7Ba%2B1%7D%7Ba%2B2%7D-++%5Cfrac%7Ba%2B5%7D%7Ba%2B6%7D%3D+%5Cfrac%7B%28a%2B1%29%28a%2B6%29-%28a%2B5%29%28a%2B2%29%7D%7B%28a%2B2%29%28a%2B6%29%7D%3D%0A%5C%5C%5C%0A%3D%5Cfrac%7Ba%5E2%2Ba%2B6a%2B6-a%5E2-2a-5a-10%7D%7B%28a%2B2%29%28a%2B6%29%7D%3D-%5Cfrac%7B4%7D%7B%28a%2B2%29%28a%2B6%29%7D%0A%5C%5C%5C%0Aa%3E0%0A%5C%5C%5C%0Aa%2B2%3E0%0A%5C%5C%5C%0Aa%2B6%3E0%0A%5C%5C%5C%0A-%5Cfrac%7B4%7D%7B%28a%2B2%29%28a%2B6%29%7D%3C0%0A%5C%5C%5C%0A+%5Cfrac%7Ba%2B1%7D%7Ba%2B2%7D%3C++%5Cfrac%7Ba%2B5%7D%7Ba%2B6%7D)
0
\\\
a+2>0
\\\
a+6>0
\\\
-\frac{4}{(a+2)(a+6)}<0
\\\
\frac{a+1}{a+2}< \frac{a+5}{a+6}" alt=" \frac{a+1}{a+2}- \frac{a+5}{a+6}= \frac{(a+1)(a+6)-(a+5)(a+2)}{(a+2)(a+6)}=
\\\
=\frac{a^2+a+6a+6-a^2-2a-5a-10}{(a+2)(a+6)}=-\frac{4}{(a+2)(a+6)}
\\\
a>0
\\\
a+2>0
\\\
a+6>0
\\\
-\frac{4}{(a+2)(a+6)}<0
\\\
\frac{a+1}{a+2}< \frac{a+5}{a+6}" align="absmiddle" class="latex-formula">